Thar Kamal: new karonda variety - Singh, Sanjay; Singh, A K; Apparao, V V; Bhargava, R (Indian Horticulture, 2019)
The karonda, Thar Kamal, has been released by Central Institute for Arid Horticulture, Bikaner, in 2015. It outperformed other varieties in flowering, fruiting and quality fruit production. The tree height and girth are 1.77 m and 23.43 cm respectively. It is spreading type, regular-bearer, dwarf and starts flowering in third year, peak flowering being third week of March. The fruits ripen in the last week of June. Fruit yield is 13.00 kg/tree. It gives 4.97 g average fruit weight, 93.66% pulp, 9.54Â° Brix TSS, 0.64% acidity, 30.41 mg/ 100g vitamin C, 6.12% total sugar and 3.87% reducing sugar.